The Attack of Alkali Silica Reaction on The Strength of Sea Water Resistance Concrete Pavement. (September 2019) - Sumarsono, A; Labib, NM; Suryoto; Setyawan, A; Zulfadli
Abstract: Aggregate is the main material in concrete slab for rigid pavement. Quality of the aggregate should be eligible for the rigid pavement. Roads with rigid pavement structure can be damaged by non-technical factors including the effect of tidal flood. That damage due to the attack of alkali silica reaction in concrete. So, it required a research to select the type of aggregate that is more resistant to alkali silica reaction that will produce concrete more resistant to sea water. The method used is this research is experimental one, some sample in alkali silica reaction test using mortar bar of (25x25x285) mm dimensions. For the testing compressive strength and flexural strength of concrete using a cube-shaped test specimens of 150mm x 150 mm and a beam shape (150x160x600)mm. For testing performed after the age of concrete 28 days for normal conditions and after a concrete immersed fresh water 28 days, then soaked in seawater 13 days, and 26 days for testing the effect of sea water on the concrete strength. The test was performed using aggregates from PT. Armada Hada Graha, Magelang and PT. Panca Dharma Puspawira, Surakarta. The conclusion at this experiment is aggregate basalt (Surakarta) is more resistant to alkali silica reaction that caused by sea water than the aggregate andesite (Magelang).